Activation and contribution of trunk and leg musculature to force production during on-water sprint kayak performance - Brown, M.; Lauder, M.; Dyson, R. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Velocity production during sprint kayaking has been shown to be dependent on the magnitude of forces produced during the stroke cycle. However, while the importance of the upper body in force production has been promoted by previous research, the importance of the trunk and lower body are yet to be established. Eight international level paddlers completed 5 on-water sprint trials during which paddle force and trunk and leg muscle activations were recorded. Significant correlations (p<0.05) were identified between peak force and peak contralateral rectus abdominus activation, while the left external oblique demonstrated significant correlations (p<0.05) with peak and mean force during both left and right paddle strokes. Results indentify that the lower trunk plays an important role in force production and therefore sprint performance.